2019
DOI: 10.1039/c9tc04282b
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted atomic layer deposition of nickel oxide as hole transport layer for hybrid perovskite solar cells

Abstract: Careful interface design and engineering are “keys” to effectively implement a conformal 10 nm plasma-assisted atomic-layer-deposited NiO film as hole transport layer in a p–i–n perovskite solar cell architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 70 publications
7
92
0
Order By: Relevance
“…[114,115] Electrodeposition, [116,117] chemical bath deposition, [118] and spray coating [119] are alternative solution-based techniques demonstrated, suitable to obtaining good performing NiO. High-performing devices have been demonstrated, also using NiO from physical methods: pulsed laser deposition, [120] e-beam deposition, [121] glancing angle deposition, [122] atomic layer deposition (ALD), [123,124] sputtering, [125,126] or even the evaporation of metallic nickel followed by oxidation in air at high temperatures. [127] The high conductivity of selective contacts is fundamental to minimize the resistive losses detrimental to the energy output of PV devices.…”
Section: Nickel Oxides (Nio X )mentioning
confidence: 99%
“…[114,115] Electrodeposition, [116,117] chemical bath deposition, [118] and spray coating [119] are alternative solution-based techniques demonstrated, suitable to obtaining good performing NiO. High-performing devices have been demonstrated, also using NiO from physical methods: pulsed laser deposition, [120] e-beam deposition, [121] glancing angle deposition, [122] atomic layer deposition (ALD), [123,124] sputtering, [125,126] or even the evaporation of metallic nickel followed by oxidation in air at high temperatures. [127] The high conductivity of selective contacts is fundamental to minimize the resistive losses detrimental to the energy output of PV devices.…”
Section: Nickel Oxides (Nio X )mentioning
confidence: 99%
“…A report by Koushik et al noted similar thermal behaviour for a Ni(MeCP) 2 PEALD process and suggested the behaviour was a consequence of a change in density. 9 To affirm this, film density between 75-325 • C was investigated by XRR. XRR measurements determined that between 75-200 • C the film density increased from 5.1-6.2g cm −3 and reduced to 5.8g cm −3 at 325 • C. It is therefore likely that the film growth rate reduces as a function of temperature due to a densification of the films.…”
Section: Resultsmentioning
confidence: 99%
“…, with oxygen plasmas respectively. 9,[20][21][22] These studies have demonstrated that conformal growth of NiO is possible with cyclopentadienyl based nickel precursors and O 2 plasma. Given the low cost of nickelocene (Ni(Cp) 2 ), it should be an attractive precursor for ALD.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also estimated a very low hole mobility (10 −5 ‐10 −3 cm 2 V −1 second −1 ) 80 . High carrier concentrations, 10 19 to 10 20 cm −3 , by Mott‐Schottky analysis have also been reported for as‐deposited films grown using aminoalkoxide and cyclopentadienyl precursors 81 . Mott‐Schottky analysis was also used to estimate the work function by flat band potential and valence band position (E VB ) of the ALD NiO x .…”
Section: Chemical Deposition Of Nickel Oxide Thin Filmsmentioning
confidence: 87%